2001
DOI: 10.1103/physrevb.63.155310
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction from CuPt-ordered III-V ternary semiconductor alloy films

Abstract: A model has been developed to describe x-ray scattering from CuPt-type ordered III-V ternary semiconductor alloys. The model takes into account the size distribution of the two different laminae-shaped variants, the random distribution of antiphase domain boundaries in each variant, and the atomic displacements due to the bond-length difference between the two constitutive binary materials. A synchrotron x-ray source was employed to measure the weak-ordering reflections from CuPt-ordered Ga 0.5 In 0.5 P and Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…␦ i is a complex function of s and can be obtained independently from a valence force field ͑VFF͒ model calculation. 12,14 For CuPt-B ordered GaInP 2 , we found that the difference in length between the In-P and the Ga-P bonds is mainly accommodated by the displacement of P atoms. The displacement of In and Ga atoms is significantly smaller.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…␦ i is a complex function of s and can be obtained independently from a valence force field ͑VFF͒ model calculation. 12,14 For CuPt-B ordered GaInP 2 , we found that the difference in length between the In-P and the Ga-P bonds is mainly accommodated by the displacement of P atoms. The displacement of In and Ga atoms is significantly smaller.…”
Section: Resultsmentioning
confidence: 95%
“…13 Debye-Waller factors, which were deduced from the Debye temperatures of GaP and InP, were included in the atomic form factors. 12 The intensity of the ordering peaks increases as the order parameter increases. On the other hand, the relative intensity of the ordering peaks is modulated by atomic displacements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PL measurements suggest an atomic ordering in the ͑In,Ga͒P layer. In order to prove this model further x-ray scattering investigations on fractional Bragg reflections 34 and transmission electron microscopy measurements are planned.…”
Section: Discussionmentioning
confidence: 98%